2008
DOI: 10.1128/iai.00101-08
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Neisseria gonorrhoeae Epithelial Cell Interactions by Vaginal Lactobacillus Species

Abstract: High levels of Lactobacillus, the dominant genus of the healthy human vaginal microbiota, have been epidemiologically linked to a reduced risk of infection following exposure to the sexually transmitted pathogen Neisseria gonorrhoeae. In this work, a cell culture model of gonococcal infection was adapted to examine the effects of lactobacilli on gonococcal interactions with endometrial epithelial cells in vitro. Precolonization of epithelial cells with Lactobacillus jensenii, Lactobacillus gasseri ATCC 33323, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 38 publications
(38 reference statements)
4
34
0
Order By: Relevance
“…This may be due to competition amongst the lactobacilli themselves, or because of alterations in adhesion. It has been reported that some bacterial species can co-colonise the surface of urogenital tract cells already colonised by lactobacilli; however, after lactobacilli are established, they can cause other species of bacterial cells to detach from the epithelium, which may offer a defence mechanism by preventing attachment of pathogens to the epithelium [29], [30]. In polymicrobial biofilms, early colonising species often promote the establishment of other species [31], [32]; however, whilst the initial interactions may be synergistic, once the biofilm is established, competition between species can result in the dominance of a single species [33].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to competition amongst the lactobacilli themselves, or because of alterations in adhesion. It has been reported that some bacterial species can co-colonise the surface of urogenital tract cells already colonised by lactobacilli; however, after lactobacilli are established, they can cause other species of bacterial cells to detach from the epithelium, which may offer a defence mechanism by preventing attachment of pathogens to the epithelium [29], [30]. In polymicrobial biofilms, early colonising species often promote the establishment of other species [31], [32]; however, whilst the initial interactions may be synergistic, once the biofilm is established, competition between species can result in the dominance of a single species [33].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lactobacilli with a higher affinity for host cell receptors can displace adherent G. vaginalis and N. gonorrhoeae 25,31 . Furthermore, some lactobacilli are thought to co-aggregate with pathogens; e.g.…”
Section: Healthy Lactobacillus Dominated Vaginal Floramentioning
confidence: 99%
“…Lactobacillus species are thought to compete for binding to receptors on host epithelial cells, and numerous studies have demonstrated that they can inhibit adherence of various urogenital pathogens including group B Streptococcus species [84], Staphylococcus aureus [84], G. vaginalis [85], N. gonorrhoeae [86], Pseudomonas aeruginosa [87], and Klebsiella pneumonia [87]. Notably, Lactobacillus species and strains vary in their ability to adhere to host cells [88] [89], which is consistent with the fact that the mechanism of competitive exclusion is only one of several defense mechanisms.…”
Section: Lactobacilli and Exclusion Of Other Bacterial Speciesmentioning
confidence: 99%
“…The absence of H 2 O 2 -producing lactobacilli has been associated with several unhealthy vaginal conditions and states including BV [36] [94], vaginal colonization of E. coli [95], preterm labor [96], and endometriosis [97]. Despite the consistent finding that H 2 O 2 -producing lactobacilli are associated with vaginal health, H 2 O 2 production was not found to be required for the lactic acid-induced inhibition of BV-associated bacteria [98], or with lactobacillus-induced inhibition of N. gonorrhoeae growth [89] [99]. O’Hanlon and colleagues [100] also reported that H 2 O 2 antimicrobial activities can be blocked by both semen and cervicovaginal fluid, which would suggest the mechanism may be ineffective in vivo .…”
Section: Lactobacilli and Exclusion Of Other Bacterial Speciesmentioning
confidence: 99%